Application of Caco-2 Cell Line in Herb-Drug Interaction Studies: Current Approaches and Challenges - Charles Awortwe; P.S. Fasinu; B. Rosenkranz (Frontiers Media S.A., 2014)
The Caco-2 model is employed in pre-clinical investigations to predict the likely gastrointestinal permeability of drugs because it expresses cytochrome P450 enzymes, transporters, microvilli and enterocytes of identical characteristics to the human small intestine. The FDA recommends this model as integral component of the Biopharmaceutics Classification System (BCS). Most dedicated laboratories use the Caco-2 cell line to screen new chemical entities through prediction of its solubility, bioavailability and the possibility of drug-drug or herb-drug interactions in the gut lumen. However, challenges in the inherent characteristics of Caco-2 cell and inter-laboratory protocol variations have resulted to generation of irreproducible data. These limitations affect the extrapolation of data from pre-clinical research to clinical studies involving drug-drug and herb-drug interactions. This review addresses some of these caveats and enumerates the plausible current and future approaches to reduce the anomalies associated with Caco-2 cell line investigations focusing on its application in herb-drug interactions.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.